Design and prototype loading and unloading mechanism for automated guided vehicle - Mohd Aizat, Mohd Azizan (2009)
Automated Guided Vehicle or AGV is one of material handling equipment that has been used widely in most manufacturing industry today as it provides more flexibility to the system. The basic concept of the AGV incorporates battery-powered and driverless vehicles with programming capabilities for path selection and positioning. They are equipped to navigate a flexible guide path network that can be easily modified and expanded. This project is focusing on the prototype the loading and unloading mechanism for the AGV, the AGV are needed to specify certain criteria that is lightweight, automatic operated and able to transport the acrylic. This loading and unloading mechanism operated using ballscrew as the movement mechanism and suction cup with vacuum pump as the adhering mechanism. The frame and main material to fabricate this AGV prototype are using the aluminium to minimize weight of the AGV. The application of the AGV in the real world application will help human and reducing cost in repetitive movement transportation activities.